Análisis multitemporal de la dinámica fluvial del cauce del río Sinú, Aguas abajo de la presa Hidroeléctrica Urrá, departamento de Córdoba, Colombia (2025)
Considering the issues in the middle basin of the main course of the Sinú River, caused by morphodynamic processes due to the action of water as a morphogenetic agent shaping the terrain (erosion and sedimentation), it is proposed to identify and calculate the river’s mobility rate based on these processes. Using Landsat 7 and Landsat 8 satellite images, the water surface was identified and classified at three different times: 2001, 2015, and 2024, allowing for a multi-temporal analysis of over 20 years.